2017
DOI: 10.1371/journal.pone.0184147
|View full text |Cite
|
Sign up to set email alerts
|

The impact of muscle relaxation techniques on the quality of life of cancer patients, as measured by the FACT-G questionnaire

Abstract: IntroductionPatients with cancer frequently suffer from emotional distress, characterized by psychological symptoms such as anxiety or depression. The presence of psychological symptoms combined with the complex nature of oncology processes can negatively impact patients’ quality of life. We aimed to determine the impact of a relaxation protocol on improving quality of life in a sample of oncological patients treated in the Spanish National Public Health System.Materials and methodsWe conducted a multicenter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(10 citation statements)
references
References 32 publications
0
7
0
3
Order By: Relevance
“…This data is logical if we consider the loss of quality of life when suffering pain that is more or less intense over a prolonged period of time. Several publications relate pain with anxiety as this involves an important loss of quality of life of patients with cancer [16][17][18]. On occasion, pharmacological treatments for pain and anxiety can be the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data is logical if we consider the loss of quality of life when suffering pain that is more or less intense over a prolonged period of time. Several publications relate pain with anxiety as this involves an important loss of quality of life of patients with cancer [16][17][18]. On occasion, pharmacological treatments for pain and anxiety can be the same.…”
Section: Discussionmentioning
confidence: 99%
“…Some of our patients practiced relaxation techniques to control anxiety symptoms. Indeed, following this perspective, Parás-Bravo et al, reported quality of life improvements via an intervention for the reduction of anxiety in cancer patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Most failures due to discontinuation of chemotherapy or reduction of the standard dosage are generally caused by clinical complications in patients undergoing treatment or by reduced performance status. Improved QoL and cardiovascular status predispose the patient to fully cope with the necessary chemotherapy protocol and, consequently, the likelihood of a successful outcome is increased [43][44][45][46][47][48]. There is no clear evidence of a direct relationship between physical activity and remission in pcALCL, but it is certainly an excellent support for specific treatments of this oncological pathology and all other indolent neoplasms in elderly patients [43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…PMR is an efficacious treatment for a range of populations and symptoms (Campos de Carvalho, Martins, & dos Santos, 2007;Carey & Burish, 1987;Isa, Moy, Razack, Zainuddin, & Zainal, 2013;Kim et al, 2016;Molassiotis, 2000;Parás-Bravo et al, 2017). Reviews of the efficacy of PMR for healthy older adults (Klainin-Yobas, Oo, Yew, & Lau, 2015) and individuals with severe psychological disorders (Vancampfort et al, 2013) have concluded that PMR can significantly reduce state and trait anxiety, depression, and psychological distress.…”
Section: Progressive Muscle Relaxation Interventions For Health Populmentioning
confidence: 99%